Novel porcine model of Crohn's disease anastomotic stricture suitable for evaluation and training of advanced endoscopic techniques - Lukas, Martin; Kolar, Martin; Ryska, Ondrej; Juhas, Stefan; Juhasova, Jana; Kalvach, Jaroslav; Pazin, Jaroslav; Kocisova, Tereza; Foltán, Ondřej; Kristianova, Hana; Ptacnik, Jan; Vitkova, Ivana; et al. (Gastrointestinal endoscopy, 2021)
BACKGROUND AND AIMS: Currently, treatment options in postsurgical recurrence of stricturing Crohn's disease (CD) are limited. However, development of new invasive endoscopic techniques in clinical practice has safety constraints. The aim of this study was to create a large animal model of anastomotic stricture with CD properties to enable development of new techniques and training. METHODS: A side-to-side ileocolonic anastomosis was created in a modified Roux-en-Y manner with bowel continuity preserved. Two weeks after surgery, we began endoscopic submucosal injections of phenol/trinitrobenzenesulfonic acid solution. This solution was injected every 2 weeks in each quadrant of the anastomosis until development of a stricture. The anastomosis site was assessed endoscopically 2 weeks after the last application (baseline) and then every 2 months until month 6. Endoscopically nonpassable strictures were treated with balloon dilation, endoscopic stricturotomy, and stent placement to confirm the feasibility of such interventions. RESULTS: Nineteen minipigs were included with no postoperative adverse events. After a mean of 4.4 ± .7 injection sessions with 10.5 ± 3.0 mL of the solution, anastomotic strictures were created in 16 pigs (84.2%). Mean diameter of the strictures at baseline was 11.6 ± 2.2 mm. The strictures were inflamed, and the endoscope could not pass. Follow-up was successfully completed in 15 animals (79.0%) with the mean deviation from the initial diameter in every measurement of -.02 ± 2.26 mm (P = .963) and a mean final diameter of 11.7 ± 3.4 mm. The histopathologic evaluation revealed the presence of submucosal fibrosis, chronic inflammation, and microgranulomas. All strictures were amenable to endoscopic therapeutic interventions. CONCLUSIONS: We developed a novel, reproducible porcine model of anastomotic stricture with histologically verified changes mimicking CD and stable diameter for more than 6 months. It is suitable for further endoscopic interventions.
Keywords: Animals; Swine, Miniature; Dilatation; výsledek terapie; endoskopie; lidé; miniaturní prasata; Constriction, Pathologic; prasata; Treatment Outcome; retrospektivní studie; Crohn Disease; Swine; Endoscopy; dilatace; Crohnova nemoc; zvířata; Retrospective Studies; stenóza; Humans